Simplifications in Selected Accounting Policies in Micro and Small Entities in Poland: Legal Regulations and Cognitive Biases - Czaja-Cieszyńska, Hanna; Mućko, Przemysław (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: To assess the impact of two factors – legal regulations and cognitive errors among decision-makers – on the choice of simplifications in the accounting policy of micro and small entities.Research Design & Methods: Content analysis of disclosed accounting policy among micro and small entities in Poland was done in order to uncover simplifications the entities made in their accounting policy. Sampling was done using the Orbis Europe database; the sample size was 100 units.Findings: Only half of the eligible companies prepare abridged financial statements. Moreover, entities apply simplifications to which they are not entitled: restrictions on the application of the prudence principle and unconditional application of tax depreciation rates to the measurement of fixed assets are not allowed for the companies surveyed.Implications / Recommendations: This research shows that those responsible for accounting policy, when deciding on the scope of the simplifications, employ cognitive biases – including status quo bias, primacy effect and confirmation bias – resulting from heuristic thinking.Contribution: The contribution’s originality is based on the results of an empirical study of simplifications in the accounting policies of micro and small entities and the explanation of these results through the lens of decision-makers’ cognitive errors. Conclusions drawn from the research can be used both by legislators in reviewing legal regulations, and by managers charged with shaping accounting policy and applying simplifications.